Clinical Epidemiology Characteristics and Antibiotic Resistance Associated with Urinary Tract Infections Caused by E. coli - Sang Ngoc Nguyen; Huyen Thanh Thi Le; Tam Duc Tran; Lam Tung Vu; Tho Huu Ho (International Journal of Nephrology)
Introduction. In individuals with urinary tract infections, Escherichia coli (E. coli) is an ubiquitous causative agent and antibiotic resistance is on the rise throughout the world. Therefore, early diagnosis and appropriate choice of antimicrobials are essential. The purpose of our study is to describe some of the clinical and epidemiological characteristics and the laboratory test results of children treated in our hospital for urinary tract infections caused by E. coli. Methods. The study included 128 patients from 2 months to 15 years of age with urinary tract infections caused by E. coli and treated at the Haiphong Children’s Hospital during the periods of 2011–2013 and 2018–2020. Results. During the two study periods, 57 and 71 cases, respectively, were included. The most common clinical symptom was fever in 40 and 46 cases, respectively. The proportion of E. coli’s resistance to ampicillin increased from 85.3% in 2011–2013 to 97.1% in 2018–2020. In 2011–2013, 70.5% of E. coli isolates were resistant to cotrimoxazole, which increased to 81.4% during 2018–2020. During both periods, E. coli was highly sensitive to amikacin, at 87% and 95.5%, respectively. In 2018–2020, carbapenems (meropenem and imipenem) and piperacillin were also effective against E. coli. Conclusion. Our study revealed that high fever was the most prevalent clinical characteristic in urinary tract infections caused by E. coli in children and E. coli was mostly resistant to ampicillin, nalidixic acid, and cotrimoxazole but was highly sensitive to ciprofloxacin, amikacin, piperacillin, meropenem, and imipenem.